Kebijakan Pemberian Kompensasi Terhadap Pekerja Perjanjian Waktu Tertentu di Kabupaten Karimun - Oktavia, Ariani; Sudirman, Lu; Girsang, Junimart (Fakultas Syariah INSURI Ponorogo, 2023)
In 2020, Law Number 11 of 2020 concerning Job Creation has been enacted. With this, it also changes the legislation regarding employment, including Government Regulation Number 35 of 2021. The purpose of this research is to find out the implementation of Government Regulation Number 35 of 2021 concerning PKWT, Outsourcing, WKWI, and PHK after the Constitutional Court Decision on Providing Compensation for PKWT Workers and providing solutions in accordance with the laws and regulations and facts found in the field in order to overcome the obstacles that occur. This research uses the Empirical/Sociological type of legal research because the data to be used is mainly data obtained directly which is primary data. Compensation is the right of workers who are bound by a Fixed-Term Employment Agreement (PKWT), so employers are obliged to provide the rights of PKWT workers at the end of the working period in accordance with the employment agreement. If the employer does not pay compensation rights, administrative sanctions will be imposed in accordance with applicable regulations.